Social interactions in a pandemic - Laura Alfaro; Ester Faia; Nora Lamersdorf; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Externalities and social preferences, such as patience and altruism, play a key role in the endogenous choice of social interactions, which in turn affect the diffusion of a pandemic or patterns of social segregation. We build a dynamic model, augmented with an SIR block, in which agents optimally choose the intensity of both general and group-specific social interactions. The equilibria in the baseline and the SIR-network model result from a matching process governed by optimally chosen contact rates. Taking into account agents' endogenous behavior generates markedly different predictions relative to a nave SIR model. Through a planner's problem, we show that neglecting agents' response to risk leads to misguided policy decisions. Mobility restrictions beyond agents' restraint are needed to the extent that aggregate externalities are not curtailed by social preferences.
Keywords: D62; D64; D85; D91; E70; I10; I18; 330; social interactions; pandemics; SIR network models; social preferences; social planner; targeted policies